Factors affecting awareness of phishing among Generation Y / Nur Farhana Mohd Zaharon, Mazurina Mohd Ali and Suhaily Hasnan - Mohd Zaharon, Nur Farhana; Mohd Ali, Mazurina; Hasnan, Suhaily (Universiti Teknologi MARA, 2021)
The purpose of this study was to determine the factors affecting awareness of phishing among Generation Y in Malaysia. Specifically, this study identified three factors that may influence awareness of phishing by applying the Theory of Technology Threat Avoidance. The factors are social engineering, anti-phishing knowledge, and security concern. Data was collected through a questionnaire survey. This study found that all the factors significantly influenced awareness of phishing among Generation Y in Malaysia. The findings of this study provide a further understanding of the factors that affect awareness of phishing. This study would benefit the public, especially Generation Y, the government, and all types of businesses, including financial institutions, by raising awareness of phishing and reducing phishing attacks.